Institutional Performativity Pressure and First-Year Teachers - Gray, Pennie L.; Seiki, Sumer (Frontiers in Education, 2020)
The challenges of negotiating the first year of teaching is something that concerns not only nascent teachers, but also many teacher educators and school administrators (Dugas, 2016). This case study of two beginning teachers explores the ways these teachers navigated the pressures of institutional performativity. Interviews reveal that both teachers’ identities were impacted by the external data-driven learning measures. The first-year teachers wrestled with the quantifiable data that served as evidence of their merit. At times, these external expectations created a crisis in values in that the beginning teachers felt they must abandon what they knew to be effective practices and instead adopt their school norms or approaches that would meet these external demands. This research points to the ways teacher educators and school administrators must work alongside beginning teachers to be a catalyst for systemic change toward student-centered learning and away from an over emphasis on student data driving teacher merit.